Structure reveals a regulation mechanism of plant outward-rectifying K + channel GORK by structural rearrangements in the CNBD–Ankyrin bridge - Taro Yamanashi; Yuki Muraoka; Tadaomi Furuta; Tsukasa Kume; Natsuko Sekido; Shunya Saito; Shota Terashima; Takeshi Yokoyama; Yoshikazu Tanaka; Atsushi Miyamoto; Kanane Sato; Tomoyuki Ito; et al. (Proceedings of the National Academy of Sciences, 2025)
Guard cells, which regulate stomatal apertures in plants, possess a sophisticated mechanism for regulating turgor pressure. The outward-rectifying “K + out ” channel GORK, expressed in guard cells of the plant Arabidopsis thaliana , is a central component that promotes stomatal closure by releasing K + to the extracellular space, thereby lowering turgor pressure. To date, the structural basis underlying the regulation of the K + transport activity of GORK is unclear. Using cryo-EM, we determined the structures of the GORK outward-rectifying K + channel with a resolution of 3.16 to 3.27 Å in five distinct conformations that differ significantly in their C-terminal cyclic nucleotide binding domain (CNBD) and ankyrin repeat (ANK) domain. The C-linker connects the transmembrane domains to the C-terminal domains, i.e., CNBD, CNBD–Ankyrin bridge, and ANK. The structural changes and interactions in the C-linker determine whether the closed state of GORK is closer to the preopen state or in a more removed state from the open state of the channel. In particular, interconversion in the short sequence within the CNBD–Ankyrin bridge plays a decisive role in this determination. This region forms an α-helix in the preopened state, while it adopts a nonhelical structure in further distant closed states. The dynamics of the cytosolic region strongly suggest that the K + channel activity of GORK is regulated by cytosolic signaling factors during stomatal closure.